Study on Dual-layer Microstrip Antenna Design for Wireless Communications - Ghadah M. Faisal (New Approaches in Engineering Research Vol. 9, 2021)
The current study involves the design of a triple band, dual layer Microstrip Patch Antenna. The purpose of this antenna is to radiate and receive electromagneticenergy in microwave range and it plays an important role in wireless communication applications. The three bands have frequencies of 0.9GHz, 1.798GHz, and 2.402GHz. The S-parameter, gain characteristics, and radiation pattern are studied. It is suggested that the proposed antenna be utilised in a mobile phone device that spans three frequency bands, including GSM 900 (889-960), GSM 1800 DCS 1800 (1710-1885), Bluetooth and Wi-Fi/WLAN (IEEE 802.11 b/g/n) ISM 2450 (Industrial, Scientific and Medical) (2400-2500). The proposed antenna has return loss(RL) of -17.79dB at 0.9 GHz; -18.5 dB RL at 1.798 GHz; and -44.2 dB RL at 2.4 GHz which are encouraging results. The suggested antenna was designed and simulated using the CST software package. Finally, three bandwidths are obtained, and the antenna exhibits promising results in WLAN applications.